2007
DOI: 10.1016/j.mib.2007.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Rhoptries: an arsenal of secreted virulence factors

Abstract: Apicomplexan parasites use actin-based motility coupled with regulated protein secretion from apical organelles to actively invade host cells. Critical in this process are rhoptries, club-shaped secretory organelles that discharge their contents during parasite invasion into host cells. A proteomic analysis of the rhoptries in Toxoplasma gondii demonstrated that this organelle contains a number of novel rhoptry proteins (ROP) including serine-threonine kinases and protein phosphatases. A subset of ROP proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
143
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(151 citation statements)
references
References 33 publications
2
143
0
6
Order By: Relevance
“…Sexual crosses between members of these lineages (Type I × Type III and Type II × Type III) (6, 7) have shown that virulence in mice segregates among F1 progeny (8). This has allowed for the discovery of a number of virulence loci using quantitative trait loci (QTL) mapping (9, 10).Toxoplasma secretes an arsenal of effector proteins into its host cell from specialized secretory organelles termed rhoptries and dense granules (11)(12)(13)(14). Given the selective pressure of the interaction with its varied hosts, it is not surprising that many of Toxoplasma's effectors are among the most polymorphic proteins between the major strains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual crosses between members of these lineages (Type I × Type III and Type II × Type III) (6, 7) have shown that virulence in mice segregates among F1 progeny (8). This has allowed for the discovery of a number of virulence loci using quantitative trait loci (QTL) mapping (9, 10).Toxoplasma secretes an arsenal of effector proteins into its host cell from specialized secretory organelles termed rhoptries and dense granules (11)(12)(13)(14). Given the selective pressure of the interaction with its varied hosts, it is not surprising that many of Toxoplasma's effectors are among the most polymorphic proteins between the major strains.…”
mentioning
confidence: 99%
“…Toxoplasma secretes an arsenal of effector proteins into its host cell from specialized secretory organelles termed rhoptries and dense granules (11)(12)(13)(14). Given the selective pressure of the interaction with its varied hosts, it is not surprising that many of Toxoplasma's effectors are among the most polymorphic proteins between the major strains.…”
mentioning
confidence: 99%
“…5 Many studies have examined the function of ROPs, but few have studies the function of GRAs. 6 In this study, we investigate variation in the expression of GRA1 and in the rate of cell apoptosis during T. gondii invasion into HeLa cells.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are Rhoptry bulb proteins (i.e. ROP16, ROP18 and ROP5) and they are secreted into host cell cytoplasm, often at the onset of cell invasion before complete internalization, and further subvert host cellular functions (Bradley and Sibley, 2007). Aside from these Rhoptry proteins, a member of the dense granule (DG) protein family, GRA15 was shown to positively activate NF-kB (p65/RelA subunit) and IL-12 production (Melo et al, 2011;Rosowski et al, 2011).…”
Section: Introductionmentioning
confidence: 99%